Genetic diversity of SAD and FAD genes responsible for the fatty acid composition in flax cultivars and lines - Dmitriev, Alexey A; Kezimana, Parfait; Rozhmina, Tatiana A; Zhuchenko, Alexander A; Povkhova, Liubov V; Pushkova, Elena N; Novakovskiy, Roman O; Pavelek, Martin; Vladimirov, Gleb N; Nikolaev, Evgeny N; Kovaleva, Oxana A; Kostyukevich, Yury I; et al. (Bmc plant biology, 2020)
BACKGROUND: Flax (Linum usitatissimum L.) is grown for fiber and seed in many countries. Flax cultivars differ in the oil composition and, depending on the ratio of fatty acids, are used in pharmaceutical, food, or paint industries. It is known that genes of SAD (stearoyl-ACP desaturase) and FAD (fatty acid desaturase) families play a key role in the synthesis of fatty acids, and some alleles of these genes are associated with a certain composition of flax oil. However, data on genetic polymorphism of these genes are still insufficient. RESULTS: On the basis of the collection of the Institute for Flax (Torzhok, Russia), we formed a representative set of 84 cultivars and lines reflecting the diversity of fatty acid composition of flax oil. An approach for the determination of full-length sequences of SAD1, SAD2, FAD2A, FAD2B, FAD3A, and FAD3B genes using the Illumina platform was developed and deep sequencing of the 6 genes in 84 flax samples was performed on MiSeq. The obtained high coverage (about 400x on average) enabled accurate assessment of polymorphisms in SAD1, SAD2, FAD2A, FAD2B, FAD3A, and FAD3B genes and evaluation of cultivar/line heterogeneity. The highest level of genetic diversity was observed for FAD3A and FAD3B genes - 91 and 62 polymorphisms respectively. Correlation analysis revealed associations between particular variants in SAD and FAD genes and predominantly those fatty acids whose conversion they catalyze: SAD - stearic and oleic acids, FAD2 - oleic and linoleic acids, FAD3 - linoleic and linolenic acids. All except one low-linolenic flax cultivars/lines contained both the substitution of tryptophan to stop codon in the FAD3A gene and histidine to tyrosine substitution in the FAD3B gene, while samples with only one of these polymorphisms had medium content of linolenic acid and cultivars/lines without them were high-linolenic. CONCLUSIONS: Genetic polymorphism of SAD and FAD genes was evaluated in the collection of flax cultivars and lines with diverse oil composition, and associations between particular polymorphisms and the ratio of fatty acids were revealed. The achieved results are the basis for the development of marker-assisted selection and DNA-based certification of flax cultivars.
Keywords: genetická heterogenita; mastné kyseliny; DNA, Plant; Fatty Acids; substituce aminokyselin; Amino Acid Substitution; alpha-Linolenic Acid; Mixed Function Oxygenases; Genetic Variation; rostlinné geny; kyselina alfa-linolenová; Fatty Acid Desaturases; len; DNA rostlinná; Sequence Analysis, DNA; Flax; Genetic Heterogeneity; sekvenční analýza DNA; desaturasy mastných kyselin; genetická variace; oxygenasy se smíšenou funkcí; Genes, Plant